Infrared variability due to magnetic pressure-driven jets, dust ejection and quasi-puffed-up inner rims. Issue 3 (12th February 2020) - Liffman, Kurt; Bryan, Geoffrey; Hutchison, Mark; Maddison, Sarah T
ABSTRACT: The interaction between a YSO stellar magnetic field and its protostellar disc can result in stellar accretional flows and outflows from the inner disc rim. Gas flows with a velocity component perpendicular to disc mid-plane subject particles to centrifugal acceleration away from the protostar, resulting in particles being catapulted across the face of the disc. The ejected material can produce a 'dust fan', which may be dense enough to mimic the appearance of a 'puffed-up' inner disc rim. We derive analytical equations for the time-dependent disc toroidal field, the disc magnetic twist, the size of the stable toroidal disc region, the jet speed, and the disc region of maximal jet flow speed. We show how the observed infrared variability of the pre-transition disc system LRLL 31 can be modelled by a dust ejecta fan from the inner-most regions of the disc whose height is partially dependent on the jet flow speed. The greater the jet flow speed, the higher is the potential dust fan scale height. An increase in mass accretion on to the star tends to increase the height and optical depth of the dust ejection fan, increasing the amount of 1–8 µm radiation. The subsequent shadow reduces the amount of light falling on the outer disc and decreases the 8–40 µm radiation. A decrease in the accretion rate reverses this scenario, thereby producing the observed 'see-saw' infrared variability.